- 鐵幣
- 2765 元
- 文章
- 698 篇
- 聲望
- 385 枚
- 上次登入
- 11-3-28
- 精華
- 0
- 註冊時間
- 05-2-15
- UID
- 110237
|
2.(x^2+x+2)/[(x-1)^3]=a/(x-1) +b/[(x-1)^2] +c/[(x-1)^3],求(a,b,c)=?
a/(x-1) +b/[(x-1)^2] +c/[(x-1)^3=(ax^2-2ax+a+bx-b+c)/(x-1)^3
因為(ax^2-2ax+a+bx-b+c)/(x-1)^3=(x^2+x+2)/[(x-1)^3]
所以a=1,b-2a=1,a-b+c=2
代入a=1,得b=3,c+1-b=2
代入b=3,得c=4
所以(a,b,c)=(1,3,4)
1.(x+2)/[(x^2 -1)(x-1)]=a/(x+1) + b/(x-1) + c/[(x-1)^2],求a+b+c=?
a/(x+1) + b/(x-1) + c/[(x-1)^2]=(a+b)x^2+(b+c-2a)x+(a-b+c)/(x^2-1)(x-1)
因為(a+b)x^2+(b+c-2a)x+(a-b+c)/(x^2-1)(x-1)=(x+2)/[(x^2 -1)(x-1)]
所以得a+b=0,b+c-2a=1,a-b+c=2
解方程後,得a=1/5,b=-1/5,c=8/5
所以a+b+c=8/5
[ 本文最後由 aeoexe 於 07-8-17 09:27 PM 編輯 ] |
|